(untitled) - Nemrava, Daniel (Romanica Olomucensia, 2012)
The article proposes an allegoric interpretation of the experimental novel La revolución es un sueño eterno (The Revolution is an Eternal Dream, 1987), a masterpiece by the Argentinian writer Andrés Rivera (1928). Our hypothesis is that rather than an attempt to fill in the empty spaces of the Argentinian official 19th century historiography, Rivera uses the memories of a history-based character Juan José Castelli to reflect upon the existential crisis of a modern man. In our opinion, the fragmentary and labyrinthine nature of the text, the splitting of the narrator and the chronotopic distortion thematize the process of creative writing itself and its crisis. We consider various concepts of allegoric phenomenology to be the most appropriate way to approach this problem.
Keywords: experimental novel; Argentina; The May Revolution; allegory; melancholy.